People's Republic of China-Hong Kong Special Administrative Region : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, Insurance Supervision, Payment Systems, Securities Settlement Systems, Monetary and Financial Policy Transparency, Corporate Governance, and Anti-Money Laundering and Combating the Finance of Terrorism. (IMF Staff Country Reports; Country Report, 2003)
This paper evaluates key findings of the Financial System Stability Assessment for Hong Kong Special Administrative Region (SAR), including Reports on the Observance of Standards and Codes on Banking Supervision, Securities Regulation, Insurance Supervision, Payment Systems, Securities Settlement Systems, Monetary and Financial Policy Transparency, and Corporate Governance. Overall, the financial system in Hong Kong SAR is resilient, sound, and overseen by a comprehensive supervisory framework. The banking system is sufficiently well capitalized and profitable to be able to withstand the more likely macroeconomic shocks, although some pressures on bank profits are emerging.